The effect of drought stress and nitrogen fertilization on the active ingredient, chlorophyll A and B, and chlorophyll index of henna (Nexo Revista Científica, 2020)
The response of active ingredient, chlorophyll a and b contents, and chlorophyll index of henna to different rates of N fertilization and drought stress was explored in a split-split-plot experiment based on a randomized complete block design with four replications in the research farm of Jiroft Branch, Islamic Azad University, Jiroft, Iran in the 2016-2017 growing season. In the current study, the main plot was assigned to drought stress at three levels (including irrigation to supply 100%, 75% or 50% of plant water requirement), the sub-plot was assigned to N fertilization at three rates (50, 100 or 150 kg ha-1 pure N), and the sub-sub-plot was assigned to ecotype at three levels (Bami, Bushehri, and Rudbari). The results showed that the effect of drought level was significant on active ingredient and chlorophyll index at the p